Hospital Nurse Scheduling Optimization Using Simulated Annealing and Probabilistic Cooling Scheme - Ferdi Chahyadi; Azhari SN; Hendra Kurniawan (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2018)
Nurse’s scheduling in hospitals becomes a complex problem, and it takes time in its making process. There are a lot of limitation and rules that have to be considered in the making process of nurse’s schedule making, so it can fulfill the need of nurse’s preference that can increase the quality of the service. The existence variety of different factors that are causing the nurse scheduling problem is so vast and different in every case. The study is aimed to develop a system used as an equipment to arrange nurse’s schedule. The working schedule obtained will be checked based on the constraints that have been required. Value check of the constraint falsification used Simulated Annealing (SA) combined with cooling method of Probabilistic Cooling Scheme (PCS). Transitional rules used cost matrix that is employed to produce a new and more efficient state. The obtained  results showed that PCS cooling methods combined with the transition rules of the cost matrix generating objective function value of  new solutions better and faster in processing time than the cooling method exponential and logarithmic. Work schedule generated by the application also has a better quality than the schedules created manually by the head of the room.